"Heaven and Earth Conspire": Grace and Nature in Sor Juana's The Divine Narcissus. Issue 2 (December 2019) - Abril, Michael Anthony
Abstract : This essay highlights the dynamic theology of nature and grace expressed within The Divine Narcissus by Sor Juana Inés de la Cruz (1651–95). Inspired by thinkers such as Augustine and Bernard of Clairvaux and, later in her life, an emphasis on the Immaculate Conception, she details an aesthetic relationship between grace and nature: human nature is created to reflect, in grace, the perfect beauty of the incarnate Son of God. Moreover, by securing positive roles for the contributions of women and for indigenous Mexican religious devotion, she highlights the way in which this dynamic between nature and grace recovers the authentic voice of the least in society—those whose voices have been unjustly suppressed by violent domination.